Analysis of electroencephalogram characteristics of anti-NMDA receptor encephalitis patients in China. Issue 7 (July 2017) - Zhang, Yan; Liu, Gang; Jiang, Meng Di; Li, Li Ping; Su, Ying Ying
Highlights: The majority of anti-NMDAR encephalitis patients (98.4%) had abnormal EEG. Diffuse slowing was the most common EEG pattern in patients with anti-NMDAR encephalitis. Extreme delta brush (EDB) mainly occurred in patients at the peak stage. Abstract: Objective: To explore the characteristics of electroencephalogram (EEG) in patients with anti-N-methyl-d -aspartate receptor (anti-NMDAR) encephalitis. Methods: Anti-NMDAR encephalitis patients admitted to the Department of Neurology between January 2012 and June 2016 were enrolled. All patients underwent electroencephalogram (EEG) at least once in the disease peak stage, and received tumor screening, symptomatic therapy, and immunotherapy. Patients received outcome evaluation every 6 months after the immunotherapy, and modified Rankin scale (mRS) 0–2 was defined as favorable outcome. Results: This study enrolled 62 cases of anti-NMDAR encephalitis patients, including 29 males (46.8%) and 33 females (53.2%). The patient ages were between 10 and 59 (mean 26.3 ± 11.3) years. A total of 93 instances of EEG monitoring were performed on 62 patients. At the peak stage, EEG presentations showed 61 cases (98.4%) were abnormal, cranial MRI showed 29 cases (46.8%) were abnormal among all 62 patients. The main presentations of abnormal EEG were diffuse slowing (25 cases, 40.3%), epileptiform discharges (11 cases, 17.7%), extreme delta brush (EDB) (10 cases, 16.1%), polymorphic delta rhythm (6 cases, 9.7%), focal slowing (5 cases, 8.1%), and diffuse beta activities (4 cases, 6.5%). Patients with normal background, epileptiform discharges, polymorphic delta rhythm, and diffuse beta activity in EEG all had favorable long-term outcome. Conclusions: The majority of anti-NMDAR encephalitis patients had abnormal EEG. EEG could sensitively reflect the abnormal brain functions of patients and could assist with early clinical diagnosis and prognosis prediction. Significance: Diffuse slowing was the most common presentation on the EEG in patients with anti-NMDAR encephalitis. The EEG pattern of normal background, epileptiform discharges, polymorphic delta rhythm, and diffuse beta activities at the peak stage might suggest favorable long-term prognosis.